FACTORS AFFECTING SMP/MTs STUDENTS’MOTIVATION TO GO INTO VOCATIONAL SCHOOLS IN SLEMAN DISTRICT - Kusworo Kusworo; Soenarto Soenarto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2016)
This research aims to find out (1) motivation, (2) factors affecting motivation and (3) the most dominant factor affecting the motivation of Junior High School (SMP / MTs) students to Vocational Schools. This research belongs to cross-sectional survey. The population of this research is 12.037 of Grade VIII students from122 SMP/MTs at Sleman District. The research sample is 338 students who are taken randomly and proportionally. The instrument used is questionnaire with likert-scale and rating-scale. Data analysis techniques used are descriptive analysis, regression analysis and partial correlation analysis. Research results show that: (1) motivation of SMP/MTs students to go into Vocational School is good, the average is 73.40%; (2) factors affecting the motivation are social economic status of student’s parents, mass media, student’s environment, and students’ individual characteristics with 72.5% and the rest which is 27.5% is affected by other factors; (3)the most dominant factor is students’ individual characteristics, and then followed by mass media factor, social economic status of students’ parents and students’ environment.